Effect of using the conversation project as a teaching tool to increase graduate student nurses' self confidence in discussing end-of-life wishes with patients and families - O'Sullivan, Cynthia; O'Shea, Eileen (Nursing Research, 2019)
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Evaluation of an innovative curriculum enhancement: The conversation project - Pagano, Michael; Manger, Diana R.; O'Shea, Eileen; O'Sullivan, Cynthia (Nursing Education Perspectives, 2020)
Two northeast nursing schools piloted an innovative curriculum to teach The Conversation Project (TCP) to the next generation of nurses. The goal was to educate 26 graduate nursing students about how to have end-of-life and advance care planning conversations with people before they experience a crisis. The focus of assignments was on communicating newly learned TCP information. Postreflections demonstrated that participants felt their communication skills had been enhanced while their anxieties were reduced. The students' abilities to have end-of-life conversations increased. © Lippincott Williams & Wilkins.
Keywords: Advance Care Planning; Communication; Conversation Project; Curriculum; End-of-Life Care; Graduate Nursing Education; Humans; Learning; Schools, Nursing; Students, Nursing; adult; advance care planning; anxiety; article; clinical article; communication skill; conversation; curriculum; dept.nur; female; graduate nursing student; human; interpersonal communication; learning; male; nursing education; nursing student; peer-reviewed